2019
DOI: 10.1002/ajh.25544
|View full text |Cite
|
Sign up to set email alerts
|

High NPM1 mutant allele burden at diagnosis correlates with minimal residual disease at first remission in de novo acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) with mutated NPM1 is a newly recognized separate entity in the revised 2016 WHO classification, and is associated with a favorable prognosis. While previous studies have evaluated NPM1 in a binary fashion, we recently demonstrated a significant independent negative prognostic effect of high NPM1 mutant allele burden (VAF) at diagnosis in a cohort of de novo AML patients. Although the importance of minimal residual disease (MRD) monitoring in NPM1‐mutated AML has been well character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…We also verified if the allelic burden calculated for NPM1 mutations (variant allelic fraction, VAF ≤ 0.4 or > 0.4) could have an impact on outcome as recently reported [ 17 ] but we did not observe any correlation between NPM1 VAF and clinical outcome in our cohort of patients. By multivariate analysis ( Table 3 ), the positive effect on survival of an aberrant NPM1 and a double mutated CEBPA was confirmed.…”
Section: Resultssupporting
confidence: 86%
“…We also verified if the allelic burden calculated for NPM1 mutations (variant allelic fraction, VAF ≤ 0.4 or > 0.4) could have an impact on outcome as recently reported [ 17 ] but we did not observe any correlation between NPM1 VAF and clinical outcome in our cohort of patients. By multivariate analysis ( Table 3 ), the positive effect on survival of an aberrant NPM1 and a double mutated CEBPA was confirmed.…”
Section: Resultssupporting
confidence: 86%
“…Moreover, their study showed that FLT3/ITD mutations in combination with the type-A mutation have much poorer prognosis when compared to FLT3/ITD mutations with type B and D cases. Recently, Patel et al 31,32 have reported that high variant allele frequency of NPM1 predict poor outcomes in de novo AML and the effect is not affected by FLT/ITD. Murine model studies have showed that mutant NPM1 and FLT3/ITD exhibit a marked and potent molecular synergy toward driving AML pathogenesis 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies utilizing NGS for the detection of MRD in AML vary greatly in their design and technical aspects. Cohorts studied have included AML patients undergoing allogeneic haematopoietic cell transplantation (alloHCT) (Getta et al , ; Kim et al , ; Thol et al , ; Zhou et al , ; Press et al , ), receiving standard induction chemotherapy (Klco et al , ; Gaksch et al , ; Jongen‐Lavrencic et al , ; Morita et al , ; Onecha et al , ; Rothenberg‐Thurley et al , ; Thol et al , ; Wong et al , ), receiving novel therapies in clinical trials (Levis et al , ), or having only specific mutations (Thol et al , ; Kohlmann et al , ; Salipante et al , ; Levis et al , ; Patkar et al , ; Zhou et al , ; Patel et al , ). Also, since most studies to date have had access to diagnostic samples, de novo leukaemia‐associated mutation discovery using remission samples alone remains an important unmet challenge.…”
Section: Current State Of Ngs Mrd Detection In Amlmentioning
confidence: 99%